On Detecting Cold Storage Transactions on Bitcoin's Blockchain - Sendin, Ivan da Silva (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2018)
There is a disparity between Bitcoin addresses and real-world entities: the same entity can have many addresses. In Blockchain's analysis, a common technique used for clustering addresses is to view addresses present at the input of the same transaction as a single entity. A common practice to make Bitcoin safer is the use of cold wallets. The use of cold wallets by exchanges - that control the wallets of many users - may disrupt Blockchain's current methods of analysis. In this work we define these scenarios and introduce an heuristic and an algorithm to detect these occurrences on Blockchain. We show that the data obtained using the proposed heuristic are consistent with what was expected.